Removal of suspended solids from the effluents of a shrimp farm by the Blood Ark Anadara tuberculosa (Sowerby, 1833) - Miranda, Anselmo; Voltolina, Domenico; Izaguirre Fierro, Gildardo; Osuna López, Isidro; Sandoval, Idalia (HIDROBIOLÓGICA, 2017)
The potential of Anadara tuberculosa for bioremediation of shrimp farm effluents was evaluated in five field experiments performed in a semi-intensive shrimp farm in Sonora (NW Mexico), and yielded mean filtration, clearance and biodeposition rates of 33.10 mg/h/g, 0.41 L/h/g and 31.19 mg/h/g, respectively. This study demonstrates that A. tuberculosa adults can remove the particulate matter of a semi-intensive shrimp farms effluents.